1999
DOI: 10.1359/jbmr.1999.14.7.1222
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High-Impact Exercise on Ultrasonic and Biochemical Indices of Skeletal Status: A Prospective Study in Young Male Gymnasts

Abstract: Physical activity has been proposed as one strategy to enhance bone mineral acquisition during growth. The aim of this study was to determine whether frequent impact loading associated with gymnastics training confers a skeletal benefit on pre-and peripubertal male gymnasts. We measured broadband ultrasonic attenuation (BUA, dB/MHz) at the calcaneus (CBUA); ultrasound velocity (m/s) at the calcaneus (CVOS), distal radius (RVOS) and phalanx (PVOS); serum osteocalcin (OC); total alkaline phosphatase (ALP) and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
66
0
3

Year Published

2001
2001
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(73 citation statements)
references
References 42 publications
4
66
0
3
Order By: Relevance
“…During gymnastics training the RO is highly repetitive movement (Daly, Rich, Klein, & Bass, 1999). The high frequency of performance repetition may have a significant influence on wrist pain and injury, which is often associated with a sensation of wrist stiffness (Brouwer, Mazzoni, & Pearce, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…During gymnastics training the RO is highly repetitive movement (Daly, Rich, Klein, & Bass, 1999). The high frequency of performance repetition may have a significant influence on wrist pain and injury, which is often associated with a sensation of wrist stiffness (Brouwer, Mazzoni, & Pearce, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…However, there is a lack of evidence relating to movement variability of weightbearing limb kinematics and kinetics during fundamental gymnastics skills. Daly, Rich, Klein and Bass (1999) demonstrated that gymnastics' training can be associated with on average more than 100 impacts per training session on the upper extremities.…”
Section: Introductionmentioning
confidence: 99%
“…A decrease in the mechanical loading due to prolonged immobilization or weightlessness in space reduces the bone formation rate, resulting in bone loss (1)(2)(3). On the other hand, an increase in mechanical loading causes a gain in bone density (4,5). Thus, bone tissue is sensitive to mechanical stimulation.…”
mentioning
confidence: 99%